Penerapan Metode Fuzzy Tsukamoto Untuk Penentuan Jurusan Sesuai Minat Bakat Penerimaan Siswa Baru Pada SMK - Prasastya Dwi Pamungkas; Dwi Remawati; Bebas Widada (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
In recent industrial revolution 4.0 era, work field demands for workers whose character, creative, innovative and competent so that education sector through the educational institution, specifically the Vocational Schools (SMK) is expected to produce competitive graduates in the advancement of recent work field. The graduate of Vocational Schools are demanded to have more work preparedness. Nevertheless, the more option of vocation in a Vocational School had made more complication for new students to choose the existing vocation. The selection of vocation in Vocational School is sometimes not in accordance with their talents and interests. It is to help the students choose the vocation according to their talent and interests. By taking selection on Vocational School of SMK Pancasila 5 Wonogiri as the object of study, the researcher design and develop an application to determine the vocation according to their talents and interest. This application uses fuzzy tsukamoto calculation method in its value processing and also PHP programming language in program code design. The results is the application which is capable to determine a vocation according to students’ talent and interest and also subject value as the calculation reference.